Micropulse and continuous wave diode retinal photocoagulation: visible and subvisible lesion parameters. Issue 6 (10th March 2006) - Desmettre, T J; Mordon, S R; Buzawa, D M; Mainster, M A
Abstract : Background/aim: Subvisible micropulse diode laser photocoagulation localises retinal laser damage because brief micropulses allow little time for heat conduction to spread temperature rise from the retinal pigment epithelium to the neural retina. Treatment power is often chosen as a multiple of that needed for visible continuous wave lesions. The authors measured clinical laser powers needed for visible end point micropulse and continuous wave diode laser retinal photocoagulation. Methods: Six parallel rows of 10 diode laser (810 nm) burns were made in the superior peripheral retina of six consecutive patients undergoing their initial frequency doubled Nd:YAG (532 nm) panretinal photocoagulation for proliferative or severe non-proliferative diabetic retinopathy. All photocoagulation exposures were 125 µm in retinal diameter and 0.2 seconds in duration. Micropulse exposures were performed with 500 Hz, 0.3 ms micropulses. The minimal power needed (1) for visible continuous wave diode photocoagulation was determined from two adjacent rows of laser lesions and (2) for visible micropulse diode photocoagulation from four additional adjacent rows of laser lesions. Fluorescein angiograms and red-free fundus photographs were obtained immediately and 6 days after laser photocoagulation in each patient. Calculations were performed to determine the extent to which clinical parameters exceeded ANSI Z136.1-2000 maximal permissible exposure (MPE) levels for laser exposure. Results: Continuous wave and micropulse lesions typically required 300 mW (60 mJ) and 1800 mW (54 mJ), respectively. Visible continuous wave and micropulse lesions exceeded MPE levels by multiples of 36× and 133×, respectively. Laser energies were similar for visible continuous wave and micropulse lesions. Conclusion: Visible micropulse lesions require 6× more power but roughly the same energy as visible continuous wave lesions. No significant difference was demonstrable in the minimal power needed for photographically and angiographically apparent diode micropulse lesions. MPE levels are designed to provide a 10× safety margin. This safety margin was 3.7× greater for micropulse than continuous wave diode laser photocoagulation.